2022
DOI: 10.3389/fenvs.2022.684589
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to Satellite-Based Land Cover Classification, Vegetation Quantification and Grassland Monitoring in Central Asian Highlands Using Sentinel-2 and MODIS Data

Abstract: The peripheral setting of cold drylands in Asian mountains makes remote sensing tools essential for respective monitoring. However, low vegetation cover and a lack of meteorological stations lead to uncertainties in vegetation modeling, and obstruct uncovering of driving degradation factors. We therefore analyzed the importance of promising variables, including soil-adjusted indices and high-resolution snow metrics, for vegetation quantification and classification in Afghanistan’s Wakhan region using Sentinel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…The examination of the Root Mean Square Error (RMSE) between the models obtained from the Albedo index and each of the spectral indices derived from remote sensing and field data revealed that the intensity of degradation derived from the MSAVI-Albedo index has the highest proximity to the field data with an RMSE of 0.65. This indicates a closer agreement than the other indices, NDVI and SAVI, which is consistent with Zandler et al’s study in 2022, which demonstrated that the NDVI index is not suitable for dryland with sparse vegetation covers [ 40 ]. Furthermore, the intensity of degradation obtained from the NDVI-TGSI model with an RMSE of 0.66 is higher than other models, indicating that the degradation intensity map derived from these two indices has higher accuracy compared to vegetation cover indices with Albedo [ 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…The examination of the Root Mean Square Error (RMSE) between the models obtained from the Albedo index and each of the spectral indices derived from remote sensing and field data revealed that the intensity of degradation derived from the MSAVI-Albedo index has the highest proximity to the field data with an RMSE of 0.65. This indicates a closer agreement than the other indices, NDVI and SAVI, which is consistent with Zandler et al’s study in 2022, which demonstrated that the NDVI index is not suitable for dryland with sparse vegetation covers [ 40 ]. Furthermore, the intensity of degradation obtained from the NDVI-TGSI model with an RMSE of 0.66 is higher than other models, indicating that the degradation intensity map derived from these two indices has higher accuracy compared to vegetation cover indices with Albedo [ 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, that method delivered unsatisfactory results in a study on estimation of the quality parameter starch content of the grassland species red clover from hyperspectral data [44]. Another promising method for variable reduction in ML approaches previously employed on grassland data is the Boruta algorithm [45]. Due to its high computational intensity [46], however, Boruta was ruled out for the present study.…”
Section: Discussionmentioning
confidence: 97%
“…To also include a non-parametric machine learning method in our analysis, we assessed the importance of the different variables on surface temperatures using a 500-repeated Boruta algorithm, as this is considered a powerful method for quantifying influential predictors [68,69]. In this approach, the dependent variable is modeled using random forest regression, whereby shadow variables are created by randomly shuffling original predictors, which are then compared to the performance of original variables for a quantitative importance assessment [70].…”
Section: Discussionmentioning
confidence: 99%
“…We used T diff as the dependent variable, and tree species, NDVI, and imperviousness within a 91 m radius, as outlined in Ziter et al [56], as independent variables to assess if all variables are considered important in a collective model. The performance of the model was assessed using 100-repeated, 10-fold cross-validation, which is considered to yield an unbiased error estimate [68]. Formulas for performance metrics are outlined in Zandler et al [72].…”
Section: Discussionmentioning
confidence: 99%